Study of the Relationship between Work life balance and Job Satisfaction in Coffee Shop Employees - Putridena, Adinda Salma; Prastika, Netty Dyan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Along with the development of the coffee shop business in the city of Samarinda, the job of being a coffee shop employee is also increasingly in demand among students. Students who study while working are certainly required to be able to carry out their duties and responsibilities and be able to balance their time well (work-life balance). Employees who can perform their duties, functions and time are assets that must be managed properly by the coffee shop business to make an optimal contribution. One of the main concerns in the coffee shop business is creating and maintaining employee job satisfaction. This study aims to determine the relationship between work-life balance and job satisfaction in coffee shop employees with student status in the city of Samarinda. This study used quantitaive approach. The sample in this study was 157 coffee shop employees with student status in the city of Samarinda and the sampling technique used was purposive sampling. The data collection method in this study used the work-life balance scale with a reliability value of 0.818 and a job satisfaction scale with a reliability value of 881. The results of this study used the Pearson product moment correlation which showed a correlation of 0.677 at a significant level of p < 0.05. This means that there is a significant positive correlation between work-life balance and job satisfaction for coffee shop employees with student status in the city of Samarinda.Seiring berkembangnya bisnis coffee shop di kota Samarinda, pekerjaan menjadi pegawai coffee shoppun semakin banyak diminati di kalangan mahasiswa. Mahasiswa yang kuliah sambil bekerja tentunya dituntut untuk mampu melaksanakan tugas dan tanggung jawab serta mampu menyeimbangkan waktu dengan baik. Pegawai yang mampu mengoperasikan tugas, fungsi dan waktunya merupakan aset yang harus dikelola dengan baik oleh bisnis coffee shop tersebut agar dapat memberikan kontribusi yang optimal. Salah satu yang harus menjadi perhatian utama dalam bisnis coffee shop adalah menciptakan dan memelihara kepuasan kerja pegawai. Penelitian ini bertujuan untuk mengetahui hubungan antara work-life balance dengan kepuasan kerja pada pegawai coffee shop berstatus mahasiswa di kota Samarinda. Penelitian ini menggunakan pendekatan kuantitatif. Sampel pada penelitian ini sebanyak 157 pegawai coffee shop berstatus mahasiswa di kota Samarinda dan teknik pengambilan sampel menggunakan purposive sampling. Metode pengumpulan data yang digunakan pada penelitian ini adalah skala work-lifebalance dengan nilai reliabilitas 0.818 dan skala kepuasan kerja dengan nilai reliabitas 881. Kedua skala tersebut disusun dengan modelikert, kemudian dianalisis menggunakan korelasi pearson product moment. Hasil penelitian ini menunjukkan korelasi sebesar 0.677 pada taraf signifikan p < 0.05. Artinya ada korelasi positif yang signifikan antara work-life balance dengan kepuasan kerja pada pegawai coffee shop berstatus mahasiswa di kota Samarinda.